The Paradox of No-Fault Social Insurance: A Normative-Empirical Analysis of Procedural Barriers in Indonesia's Traffic Accident Compensation Scheme - Fadlan; E Arinda Chikita (HM Publisher, 2025)
Article 28D(1) of Indonesia's 1945 Constitution guarantees legal protection and certainty. Despite Law Number 34 of 1964 establishing a progressive no-fault compensation scheme administered by Jasa Raharja, traffic accident victims frequently face insurmountable administrative barriers. This study employs a mixed normative-empirical methodology in the Barelang Police Resort jurisdiction, Riau Islands. Normative analysis utilized grammatical, historical, systematic, and teleological interpretations of statutory frameworks. The empirical phase integrated stakeholder interviews with a quantitative retrospective cohort study analyzing claim adjudication outcomes, processing durations, and documentation barriers. The statutory framework contains critical gaps. Procedural ambiguities create disproportionate documentation burdens, leading to an empirical 25.5% claim abandonment rate driven heavily by fear of vehicle seizure and civil registration irregularities. Furthermore, the categorical exclusion of single-vehicle accidents fails to account for infrastructure-related causation, violating equal treatment guarantees. Regulatory fragmentation regarding temporal standards results in systematic processing delays, compounded by severe public awareness deficits. In conclusion, the implementation of Law Number 34 of 1964 structurally transforms a theoretical no-fault scheme into a restrictive mechanism privileging legally sophisticated claimants. We propose specific statutory amendments, including integrated inter-institutional coordination mandates and enforceable processing timelines, to align the compensation framework with constitutional mandates.